LANGUAGE DEVELOPMENT OF AUTISM CHILDREN IN ISLAMIC PSYCHOANALYTIC TREATMENT (Case Study at Southeast Sulawesi Autism Service Center) - M, Sitti Fauziah; Jaya, Abdul Rahman (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
Symptoms of autism, in general, are usually detected at the age of children who have not reached three years old, with varying levels in each child, ranging from mild to severe symptoms. These symptoms include constant difficulty in socializing, communicating and interacting with others verbally, difficulty in using and understanding language, and inability in using body language to convey meaning. Therefore, even though they have reached the age when speech development should occur, the children are unable to establish conversations or interactions with other people. Children with autism tend to repeat words or phrases spoken by others without forming their speech style and not developing their language skills. The objectives to be achieved in this study were to describe the language development problems of autistic children who were currently under psychoanalytic treatment at Kendari Autism Service Center and the factors that influenced them. The research findings showed that the language development abilities of autistic children in the phonological form in obtaining vowel sounds and diphthongs were good. However, they were still lacking in obtaining consonants. More practice was needed so that they could pronounce perfect phonemes. Meanwhile, autistic children in Kendari's autistic service could master nouns with more numbers than verbal and adjectives in lexicon skills. However, the phonological process that occurred in autistic children was very slow. This happened because they were sometimes like deaf people who could not hear what people were talking about. If called, they did not want to turn around. They also did not focus on interacting with other people. For example, he would answer if he was being spoken to, but his gaze was not on the person spoken to. Almost more than half of autistic children were unable to speak well. Their speech proned to be echolalia, literal, lack rhythm, lack vowels in the word produced, replacing or removing consonants contained in a word.